A Historian on Poetry - Mitaitė, Donata (Colloquia, 2018)
Mindaugas Tamošaitis, Mes esam Šiaurės krašto.... Poetui Eugenijui Matuzevičiui (1917–1994) – 100 metų, Vilnius: Sofoklis, 2017, 383 p., ISBN 978-609-444-237-7